A study of students on the Autism Spectrum transformation in a high school transition program - Moore-Gumora, Courteny (Center for Leadership Equity and Research)
This paper shares the results of a dissertation sharing the transformative process of ten participants in a program for students with Asperger Syndrome transitioning from an urban high school setting to college, which includes the extracurricular extension referred to as Ethos. The dissertation considers the experience in the context of specialized education, and the broader contexts of curricular development and instruction concerning school reform and design. Fundamentally, the study intends to examine and explain the extent to which these students experience transformation during their transition to higher education in this progressive program. Embedded in the program design are in-depth inquiry driven discussions and experiences to enhance interpersonal relationships, effective communication, and higher level cognition. The exploration examines whether the in-depth inquiry driven design does contribute to academic and lifelong learning, fundamentally improving students over-all self-perception, empowerment, and actualization of life goals, which is the underpinning purpose of an exceptional education.